Reading the Bible as Literature A Journey - Ondich, Jody (Open textbook library., 2022)
The Bible is one of the most published books in human history. It is also one of the most misquoted, misunderstood and misused books in human history. This happens because people are not always aware that the Bible is not a book, it is a collection of diverse writings. The Bible might even be called an anthology, and it will include everything from poetry to genealogy, pithy sayings to architectural mandates, mythology to letters. Knowing what one is reading helps one understand the ideas in the writings. We read letters in the context of who wrote them and who received them. We read sermons understanding the speaker's perspective may differ from the listener's perspective. So this text is an attempt to give historic, literary, geographical and cultural context to a complex and often poorly understood set of materials. This is very much an ebook, and needs to be used in that format. Pdfs and other printed versions will lose a great deal of the content.